Applications of optical frequency-domain reflectometry technology in strain-deformed configuration conversion of structural surface deformed configuration measurement - Zhenglin Zhang; Yangyang Sun; Qinghua Zhang; Jianli Duan; Lei Gao (International Journal of Distributed Sensor Networks)
In this study, the conversion relation between deformed configuration and strain during structural monitoring was analyzed based on the basic mechanics principle of materials. A distributed fiber optic measurement system was used to measure the accurate values of structural surface strain, and then calculate the intensity of surface-deformed configuration further. An optical fiber was attached to the surface of a flexible steel ruler, and the generated strain data were used to precisely measure the endpoint-deformed configuration of the ruler. Furthermore, the calculated deformed configuration was calculated and compared with the actual deformed configuration. It was found that the curves of calculated deformed configuration basically coincided (with a relative error of less than 0.6%) with the curves of actual deformed configuration.